A chitosan fiber as green material for removing Cr(VI) ions and Cu(II) ions pollutants - Shujie Zhang (Nature Portfolio, 2021)
Abstract The application shell uses cellulose as a green and recyclable fiber material, which has great value in the field of water treatment environment. Varying factors, including pH value, dosage of CS, reaction time and original Cr(VI) ions and Cu(II) ions were studied to investigate the Cr(VI) and Cu(II) ions removal efficiency. The obtained shell trichlorocellulose has better permeability to copper ions, which is mainly due to the different oxide states of copper ions and chromium ions in a pH environment, which lead to different combinations. The price of shell cellulose neutralization is relatively low. Metal ions have better absorption properties. The kinetic and thermodynamic characteristics of the adsorption process of copper ions by chitosan yarns were discussed. The adsorption process of copper ions conformed to the quasi-second-order kinetic equation. It can be fitted by Langmuir isotherm. The adsorption of copper ions by the yarn is a spontaneous thermal reaction with both physical adsorption and chemical adsorption. Compared with chromium ions, chitosan fibers have better adsorption of copper ions, which is mainly because the amino groups in chitosan fibers can have good chelation with copper ions. SEM, FTIR, XRD were used to characterize the adsorption of copper ions by chitosan fibers, and the mechanism of the adsorption of metal ions by chitosan fibers was explored.